2007
DOI: 10.1681/asn.2007010119
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Endothelial Glycocalyx Constitutes a Barrier to Protein Permeability

Abstract: Glycocalyx, composed of glycoproteins including proteoglycans, coats the luminal surface of the glomerular capillaries. Human heparanase degrades heparan sulphate glycosaminoglycans and is upregulated in proteinuric states. In this study, we analyze the structure of the human glomerular endothelial cell glycocalyx in vitro and examine its functional relevance, especially after treatment with human heparanase. Electron microscopy of conditionally immortalized glomerular endothelial cells revealed a 200-nm thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
229
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(243 citation statements)
references
References 47 publications
13
229
0
1
Order By: Relevance
“…7 A glycocalyx influences the permeation of charged proteins over the endothelial wall. 53,54 The striking effect of desialylation of the glycocalyx by neuraminidase treatment on pH-dependent cholangiocyte toxicity induced by CDC and GCDC, but not TCDC, supports the idea that polar, negatively charged bile salts are prohibited from entering cholangiocytes and from inducing cell death. We assume that this protective effect of the intact glycocalyx is the result of local stabilization of the biliary HCO À 3 umbrella, enabling the deprotonation of bile acids to bile salts in the close vicinity to the membrane.…”
Section: Discussionmentioning
confidence: 73%
“…7 A glycocalyx influences the permeation of charged proteins over the endothelial wall. 53,54 The striking effect of desialylation of the glycocalyx by neuraminidase treatment on pH-dependent cholangiocyte toxicity induced by CDC and GCDC, but not TCDC, supports the idea that polar, negatively charged bile salts are prohibited from entering cholangiocytes and from inducing cell death. We assume that this protective effect of the intact glycocalyx is the result of local stabilization of the biliary HCO À 3 umbrella, enabling the deprotonation of bile acids to bile salts in the close vicinity to the membrane.…”
Section: Discussionmentioning
confidence: 73%
“…It has recently been reported that GEnCs are covered by an ESL, containing glycocalyx and cell coat, which extends into the fenestrae. 30,31 The ESL covers the cellular surface and is composed of large amounts of glycoprotein, such as heparan sulfate proteoglycan. 32 Because of the presence of sulfated sugar chains in heparan sulfate proteoglycan, the ESL possesses a highly negative charge and thereby regulates vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
“…7 The fenestrated endothelium in glomeruli, glomerular basement membrane, and podocytes form a physical barrier against transition of macromolecules such as albumin and the other proteins in plasma. 8,9 Given the role of VEGF in enhancing microvascular permeability, it is estimated that VEGF may regulate glomerular permeability. There is a close relationship between the distribution of fenestrae and rise in VEGF expression.…”
Section: Introductionmentioning
confidence: 99%